From the right ventricle to the descending aorta: a Case Report of complex thrombotic events in a patient with nephrotic syndrome - Chen, Jiaojiao; Zhu, Longyin; Zhou, Fen; Li, Yuting; Gu, Tao; Xia, Jing (Frontiers in Pharmacology, 2025)
BackgroundNephrotic syndrome is characterized by significant proteinuria, hypoalbuminemia, edema, and hyperlipidemia. Patients frequently exhibit hypercoagulability on account of endothelial dysfunction and abnormal blood coagulation function, which significantly heighten the risk of thrombus formation. Although anticoagulant therapy is crucial for preventing thrombotic events, formulating individualized anticoagulation treatment plans for these patients remains a challenge in clinical practice due to variations in renal function and the distinct metabolic characteristics of anticoagulant medications.Case IntroductionThis case report presents a 27-year-old male patient diagnosed with nephrotic syndrome. The etiological diagnosis was hepatitis B virus-associated glomerulonephritis, and the pathological diagnosis was mesangial proliferative glomerulonephritis. The patient had a relapse accompanied by bilateral pulmonary embolism and a right ventricular thrombus, and ultimately underwent thrombectomy. In the subsequent year, despite receiving adequate anticoagulation therapy with rivaroxaban, rare events of descending aortic mural thrombus and bilateral renal infarction occurred. The patient was treated with anticoagulation, endovascular exclusion with a descending aorta covered stent for the isolation of mural thrombus, and prolonged antiplatelet therapy. As of now, follow-up has shown no recurrence of thrombotic events.ConclusionThis case underscores the challenges associated with managing the hypercoagulability in patients with nephrotic syndrome and emphasizes the importance of personalized anticoagulation therapy. To improve patient outcomes, future research should focus on the selection of anticoagulant agents, dosage optimization, and monitoring strategies to enhance the safety and efficacy of anticoagulation treatment in this patient population.